2007
DOI: 10.1097/01.brs.0000251876.98496.52
|View full text |Cite
|
Sign up to set email alerts
|

Patientsʼ Satisfaction With Provided Care/Information and Expectations on Clinical Outcome After Lumbar Disc Herniation Surgery

Abstract: Patients undergoing lumbar disc herniation surgery are mostly satisfied with provided care before and after surgery, however, less satisfied with information provided. Further, patients with preoperative positive expectations on work return and realistic expectations on pain and physical recovery have a greater chance to be satisfied with the surgical results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
126
0
11

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(141 citation statements)
references
References 24 publications
4
126
0
11
Order By: Relevance
“…To the authors' knowledge, no study has investigated this issue in any depth in patients undergoing spine surgery. One study reported a good match between surgeons' and patients' ratings after surgery for lumbar disc herniation, but only limited details were given, especially in relation to factors that might influence the discrepancies found [15]. To this end, the data collected in surgical registries are particularly useful, since they are acquired from large numbers of patients, and from the perspective of both the patient and the surgeon.…”
Section: Introductionmentioning
confidence: 99%
“…To the authors' knowledge, no study has investigated this issue in any depth in patients undergoing spine surgery. One study reported a good match between surgeons' and patients' ratings after surgery for lumbar disc herniation, but only limited details were given, especially in relation to factors that might influence the discrepancies found [15]. To this end, the data collected in surgical registries are particularly useful, since they are acquired from large numbers of patients, and from the perspective of both the patient and the surgeon.…”
Section: Introductionmentioning
confidence: 99%
“…O uso do grau de satisfação dos pacientes com o tratamento também tem sido utilizado como parâmetro para avaliação do resultado. 18 Segundo Turner et al 19 a satisfação do paciente com o procedimento cirúr-gico pode variar de 16%-95%, com uma média de 68%.…”
Section: Resultsunclassified
“…At least 2 such studies have now found that 1 important factor in improving patient satisfaction following surgery is accurately establishing realistic patient expectations prior to surgery. 117,138 Given the increasing relevance of satisfaction metrics in advancing patient-centered measures of health care services, along with improvement opportunities identified in a large national clinical data program, accurate assessment of patients' self-reported satisfaction with care before and after therapy is essential to assess the impact of interventions and make appropriate plans for continuing individual care as well as to improve the systemic aspects of care. …”
Section: Rationalementioning
confidence: 99%